2020
DOI: 10.1101/2020.10.20.342758
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Uncovering the mechanisms of real-world attentional control over the course of primary education

Abstract: Schooling may shape children's abilities to control their attention, but it is unclear if this impact extends from control over visual objects to encompass multisensory objects, which are more typical of everyday environments. We compared children across three primary school grades (Swiss 1st, 3rd, and 5th grade) on their performance on a computer game-like audio-visual attentional control task, while recording their EEG. Behavioural markers of visual attentional control were present from 3rd grade (after 2 ye… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 70 publications
1
4
0
Order By: Relevance
“…Contrastingly, Matusz et al (2019b) have shown evidence for both brain mechanisms underlying N2pc-like responses. These and other results of ours (Turoman et al 2021a, 2021b) provided evidence from surface-level data for different brain sources contributing to the N2pc’s, a finding that has been previously shown only in source-level data (Hopf et al 2000). These findings point to a certain limitation of the N2pc (canonically analysed), which is an EEG correlate of attentional selection, but where other analytical approaches are necessary to reveal brain mechanisms of attentional selection.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…Contrastingly, Matusz et al (2019b) have shown evidence for both brain mechanisms underlying N2pc-like responses. These and other results of ours (Turoman et al 2021a, 2021b) provided evidence from surface-level data for different brain sources contributing to the N2pc’s, a finding that has been previously shown only in source-level data (Hopf et al 2000). These findings point to a certain limitation of the N2pc (canonically analysed), which is an EEG correlate of attentional selection, but where other analytical approaches are necessary to reveal brain mechanisms of attentional selection.…”
Section: Discussionsupporting
confidence: 88%
“…Like in the former study, each experimental trial consisted of the following sequence of arrays: base array (In Experiments 1 and 3: randomly varied between 100, 250, and 450ms; in Experiments 2 and 4: 450ms), followed by distractor array (50ms), followed by a fixation point (150ms), and finally a target array (50ms, see Figure 1A). However, compared to the original Matusz and Eimer (2011) paradigm, the number of elements was reduced from 6 to 4 and targets were reshaped to look like diamonds rather than rectangles, as Experiment 1 served as an adult control for a different, developmental study (reported in Turoman et al, 2020a, 2020b). Thus, the base array contained four differently coloured sets of closely aligned dots, each dot subtending 0.1° × 0.1° of visual angle.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In the pursuit of understanding of the development of attentional control in real-world environments, the two perspectives complement each other, creating a more complete picture on attentional control development. For this reason, we have recently carried out a child-centric EN analysis of the developing visual and multisensory attentional control ( Turoman et al, 2020b ). In short, we found that when using children as a reference point, already 5-year-olds show evidence of visual top-down attentional control, as measured by TAC, albeit not via adult-like brain networks.…”
Section: Discussionmentioning
confidence: 99%